Poster 156: Investigating Disparity in Follow-Up Rates of Non-Operative Treatment for Anterior Shoulder Instability. Issue 7 (30th July 2022) - Dansby, Jalen; Ahmed, Rifat; Bixby, Elise; Saltzman, Bryan; Jobin, Charles; Trofa, David
Objectives: Racial and ethnic disparities have been documented in numerous aspects of musculoskeletal care. Specifically, the Multicenter Orthopedic Outcomes Network (MOON) Shoulder Instability Group found that amongst patients undergoing surgery for anterior shoulder instability, minorities had a higher frequency of articular cartilage lesions, and increased frequencies of both glenoid bone loss >10% and Hill-Sachs lesions at the time of surgery. Loss to follow-up and failure to comply with initial non-operative management may play a role in the increased disease burden in this group. This study sought to investigate patient demographics associated with poor follow-up after initiation of nonoperative management regimens for anterior shoulder instability. We hypothesized that significant disparities would be observed with nonoperative follow-up rates. More specifically, we predicted that minority patients and those with state or federal dependent insurances such as Medicaid or Medicare will have lower rates of follow-up. Methods: After obtaining IRB approval, demographics and ambulatory care appointment data for new patient visits and subsequent follow-up encounters associated with a diagnosis of "shoulder instability" or/and "labral tear" were extracted from our electronic medical records from 01/01/2010 to 01/31/2020. National Institute of Health (NIH) guidelines were followed for race, ethnicity, and insurance type categorizations. With the standard of care for non-operative management of anterior shoulder instability ranging from 6-12 weeks of physical therapy, the optimal time window for follow-up used for analysis was defined as 4-12 weeks after the initial visit. Chi-squared tests, pairwise comparisons for multiple variables of interest, and parametric between-group comparison and analyses were performed. Results: A total of 10, 854 patient visits were identified. After excluding patients that underwent surgical intervention, a total of 2, 679 unique patients and their subsequent encounters were analyzed. These patients had a mean age of 31.4 ± 13.6 years, 77.9% were male and 43.9% were white (Table 1). Of these patients, 1, 217 (45.4%) followed up at any point and 420 (34.5%) of this subset of patients followed up within 4-12 weeks of their first visit. There was no significant difference between the overall rates of follow up of white versus minority patients (50.6% versus 49.0%, p = 0.64), nor in the rates of follow up within the optimal time window (16.6% versus 16.9%, p = 0.85) (Table 2). There was no significant difference between rates of follow-up at any point based on insurance types (commercial/ managed care, Medicaid, Medicare, self-pay, and workers compensation) (p = 0.084). However, there was a significant difference between rates of optimally timed follow-up based upon insurance type (p = 0.002) (Table 3). 23.2% of patients with Medicare or Medicaid followed up within 4-12 weeks, as compared to 17.2% of patients who paid out-of-pocket and 14.5% of patients with commercial/ managed care insurance. Conclusions: There were no significant racial disparities seen between white and minority patients in regard to the rates of non-operative follow up for anterior shoulder instability in this study. Furthermore, patients with governmental insurance plans successfully followed up within the optimal 4-12 week time period at a higher rate when compared to patients with commercial or self-pay insurance. These findings suggest that a large, urban academic tertiary care center, can successfully employ strategies to retain patients of different minority status and insurance type for follow-up. The presence of satellite clinics minimizing the distance burden of access to care, use of interpreters to bridge language gaps, and systemic implementation of comprehensive discharge instructions used at our institution may be contributing factors to the findings of the investigation. This study may be enhanced by a multicenter investigation in the future in various geographic locations with a diverse patient population and payer mix. The investigation is limited by the large overall number of patients (54.6%) who never followed up. Further investigations are needed to determine what factors may have influenced these patients to not seek follow-up within our institution. In conclusion, this study found that a single tertiary care system equitably retains patients for follow-up for treatment of their anterior shoulder instability. Further work is needed to better understand if this equitable follow-up results in similar outcomes in different patient populations at our institution, and if disparities in follow-up quantity, quality, and timing are associated with the increased burden of disease for minorities with anterior shoulder instability seen at other institutions in previous studies. Table 1. Patient Demographics (2, 679 patients) Table 2. Analysis of Follow-Up within 4-12 Week Window Stratified by Racial Groups Table 3. Analysis of Follow-Up within 4-12 Week Window Stratified by Insurance Type